Knowledge of Teledentistry Among Lecturers of Faculty of Dentistry Universitas Prof Dr Moestopo (Beragama) - Binarti, Irma; Mulyatno, Nirwan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Introduction: There are many advantages to dentistry when combined with internet and telecommunications technology. Teledentistry facilitates communication between patients and various healthcare providers. The goal is to find out how knowledgeable and how the dentistry faculty lecturers feel about teledentistry. Materials and Procedures: Making use of a self-administered structured questionnaire, descriptive Prof. Dr. Moestopo (Beragama) University's faculty of dentistry conducted a cross-sectional study with 11 items. Findings: A total of sixty people answered the survey. According to the results of the current study, there are 45 lecturers (75%) who have good knowledge of teledentistry, 12 lecturers (20%) who have fair knowledge, and 3 lecturers (5%), who have poor knowledge. In conclusion, the majority of the lecturers at the Prof. Dr. Moestopo (Beragama) University Dentistry Faculty were well-versed in teledentistry.